Don't believe the hype: a grounded exploratory six country wine purchasing study. (3rd April 2017) - Pelet, Jean-Éric; Lecat, Benoît; Khan, Jashim; Rundle-Thiele, Sharyn; Lee, Linda W.; Ellis, Debbie; Garry Wolf, Marianne M. C.; Wegmann, Anne Lena; Kavoura, Niki; Katsoni, Vicky
ABSTRACT: The purpose of this exploratory study was to understand the extent that consumers report purchasing wine on mobile devices and to empirically examine potential drivers of m-wine purchasing across six countries to guide theoretical research enquiry moving forward. Purposive sampling was employed. An online survey involving 2853 respondents from France, Germany, Greece, Canada, US and South Africa forms the basis for the current study. The results of the study indicate that though mobile phone usage, wine consumption and purchasing rates are high, mobile-wine purchasing prevalence is low within all six countries. While technology hype has us believe an online presence is essential for business revenue growth and performance; the current study indicates wineries should carefully consider consumer readiness towards mobile-wine purchasing. Limitations and recommendations for future research are identified.